PENGARUH BRAND AMBASSADOR DAN BRAND PERSONALITY TERHADAP MINAT BELI DENGAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING (Studi pada Konsumen Online Store House Of Smith Store) - Nur Chasanah, Amalia; Choirul Huda Arifa Faiz, Devan (Universitas Dian Nuswantoro, 2024)
ABSTRACT The phenomenon of choosing the House of Smith online store product is caused by product sales decreasing on average for 3 product brands in 2021-2023. This is certainly interesting to research, what factors influence buying interest in House of Smith online store products. The aim of the research is to analyze the influence of brand ambassadors, brand personality on purchasing interest with brand image as an intervening variable in House of Smith online store products. The number of samples in this study was 96 respondents, where the sampling technique used was purposive sampling technique, which is a sampling determination based on criteria determined by researchers including consumers who purchased products at the House Of Smith Store Online Store, at least 17 years old, domiciled in Semarang and have purchased at least 2 times at the Online Store House Of Smith Store. The data analysis method used is multiple linear regression. The research results show that there is a positive and significant influence of brand ambassadors on brand image, there is a positive and significant influence of brand personality on brand image, there is a positive and significant influence of Brand Ambassadors on Purchase Interest, there is a positive and significant influence of brand personality on purchase interest, and there is positive and significant influence of brand personality on buying interest. Keywords: brand ambassador, brand personality, brand image and purchase interest.